Crushed Gold Shell Nanoparticles Labeled with Radioactive Iodine as a Theranostic Nanoplatform for Macrophage-Mediated Photothermal Therapy - Lee, Sang Bong; Lee, Jae‑Eon; Cho, Sung Jin; Chin, Jungwook; Kim, Sang Kyoon; Lee, In‑Kyu; Lee, Sang‑Woo; Lee, Jaetae; Jeon, Yong Hyun (Nano-Micro Letters, 2019)
Plasmonic nanostructure-mediated photothermal therapy (PTT) has proven to be a promising approach for cancer treatment, and new approaches for its effective delivery to tumor lesions are currently being developed. This study aimed to assess macrophage-mediated delivery of PTT using radioiodine-124-labeled gold nanoparticles with crushed gold shells (124I-Au@AuCBs) as a theranostic nanoplatform. 124I-Au@AuCBs exhibited effective photothermal conversion effects both in vitro and in vivo and were efficiently taken up by macrophages without cytotoxicity. After the administration of 124I-Au@AuCB-labeled macrophages to colon tumors, intensive signals were observed at tumor lesions, and subsequent in vivo PTT with laser irradiation yielded potent antitumor effects. The results indicate the considerable potential of 124I-Au@AuCBs as novel theranostic nanomaterials and the prominent advantages of macrophage-mediated cellular therapies in treating cancer and other diseases. Highlights: 1 Crushed gold shell radionuclide nanoballs (124I-Au@AuCBs) were fabricated as unique photothermal therapeutics and nuclear medicine imaging nanoplatforms. 2 Macrophage-mediated delivery of 124I-Au@AuCBs and their potential photothermal therapy applications were demonstrated in mice with colon cancer.